Bioremediation of Wastewater 2016
DOI: 10.1201/b18618-11
|View full text |Cite
|
Sign up to set email alerts
|

- Assessing Bacterial Diversity in a Seawater-Processing Wastewater Treatment Plant by 454-Pyrosequencing of the 16S rRNA and amoA Genes

Abstract: Background: Biological WWTPs must be functionally stable to continuously and steadily remove contaminants which rely upon the activity of complex microbial communities. However, knowledge is still lacking in regard to microbial community functional structures and their linkages to environmental variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As expected, decreased bacterial diversity was observed in the MF and RO biofilms compared with the secondary effluent; i.e., the influent to the AWPF composed of activated sludge and trickling filter effluent (Q1). It is well understood that proliferation of microorganisms during the activated sludge treatment process will increase microbial activity, thereby enabling removal of organics, toxins, and nutrients (Wang et al 2014). As was observed in the current study, undisinfected Q1 influent would be expected to have greater bacterial diversity than MF and RO biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, decreased bacterial diversity was observed in the MF and RO biofilms compared with the secondary effluent; i.e., the influent to the AWPF composed of activated sludge and trickling filter effluent (Q1). It is well understood that proliferation of microorganisms during the activated sludge treatment process will increase microbial activity, thereby enabling removal of organics, toxins, and nutrients (Wang et al 2014). As was observed in the current study, undisinfected Q1 influent would be expected to have greater bacterial diversity than MF and RO biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Further screening and method assessments are needed to ensure detection and identification of all fungi present, in particular for those present in low abundance (Tan et al 2015). Previous studies using molecular techniques have identified fungi DNA in WWTPs (Kwiatkowska & Zielinska 2016, Wang et al 2014), but the current study is the first to characterize fungi DNA that is present in biofilms related to MF and RO membranes.…”
Section: Figure 5 Relative Abundance Of Bacteria Genera In Mf and Ro mentioning
confidence: 96%
“…Recently, GeoChip 3.0 and the GeoChip 4 series have been applied to the investigations of industrial WWTPs (Zhang et al 2013) and municipal wastewater treatment systems (Sun et al 2014;Wang et al 2014), respectively. The studies successfully revealed some linkages between functional potential and environmental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, bacterial community structures of aerobic sludge (A-O) and anaerobic sludge (A-A) of WWTPA were clearly separated, both of which were dramatically different from those of WWTPB. The difference in wastewater quality may result in the divergence of the aerobic sludge communities of the two WWTPs, and available oxygen is considered a crucial factor contributing to the difference between the aerobic and anaerobic sludge samples [25,26].…”
Section: Biodiversity and Functions Of Microbial Communities Of The Wmentioning
confidence: 99%